Window Shopping with Duchamp: Commodity Aesthetics Delayed in Glass - J. Brandon Pelcher (Studies in 20th & 21st Century Literature, 2019)
While Marcel Duchamp’s readymades are consistently framed as a challenge to the art world and the concept of art itself, they also challenge the world from which they were taken, the world of commodities. Readymades subject the commodity to the world of aesthetics in order to more fully investigate the commodity aesthetics of both the commodity form itself and it presentation in shop window displays. This critical investigation complicates the role of commodity aesthetics and consumption as well as their formation of the consumer-subject in Fordist capitalism. The readymade can be seen both as an important forerunner to the theories of commodity aesthetics and consumption in the 1960s and 70s as well as as exemplary of contemporaneous Dadaist praxis.
Keywords: Duchamp; readymades; commodity aesthetics; shop window; Dada